ANALISA BENTUK FURNITURE SEBAGAI MEDIA DUDUK PADA AREA FOODTRUCK - Desy Dwi Putri (Ide dan Dialog Desain Indonesia (Idealog), 2018)
Basically the application of Foodtruck in modern society is classified as a sales medium that is required to move freely with consideration of location that can change, in the application of foodtruck design must include efficiency in mobilization and interior that is in accordance with the character of foodtruck , namely the use of interior elements as optional gasket that must be considered in the foodtruck design method, including furniture thatdominates the layout of the room. Furniture design in the foodtruck area becomes the foundation in the form of rules that answer the problem of an activity. The process to produce an object that has a high value of economic, aesthetic and functional. In the method of applying geometry to a stoolcan be used as a reference in construction, supporting activities, capacity and integrity of the results of a design process, in the stoolthere are some basic problem identification and relevance to the geometry transformation process and examine any errors that must be avoided in a stooldesign with the aim of meeting standards, to minimize errors in a design concept stoolthat plays in the scope of geometry and shape transformation